Serum copper and zinc levels and the risk of oral cancer: A new insight based on large‐scale case–control study. (6th September 2018) - Chen, Fa; Wang, Jing; Chen, Jinfa; Yan, Lingjun; Hu, Zhijian; Wu, Junfeng; Bao, Xiaodan; Lin, Liangkun; Wang, Rui; Cai, Lin; Lin, Lisong; Qiu, Yu; et al.
Abstract: Objective: Limited evidence exists on the roles of serum copper (Cu) and zinc (Zn) in oral cancer risk. We aimed to preliminarily explore the association between serum Cu and Zn levels and oral cancer risk with relatively large‐scale samples. Methods: Serum Cu and Zn levels of 344 oral cancer patients and 1, 122 matched healthy controls in this case–control study were measured by inductively coupled plasma mass spectrometry (ICP‐MS). Results: Restricted cubic spline revealed the U ‐shaped relationship between serum Cu or Zn levels and the risk of oral cancer. Serum deficient or elevated levels of Cu were significantly associated with the risk of oral cancer: The ORs were 1.38 (95% CI: 1.01–1.89) and 2.82 (95% CI: 1.60–4.98), respectively. The positive association of serum low or high levels of Zn with oral cancer risk was also observed: The ORs were 2.72 (95% CI: 1.60–4.62) and 12.41 (95% CI: 9.09–16.93), respectively. Additionally, there were multiplicative interactions between the aforementioned trace elements and smoking. Conclusions: This preliminary study suggests that both serum excess and deficient levels of Cu or Zn were significant correlation with oral cancer risk, which may provide a new insight on the roles of serum Cu and Zn in oral cancer.